MOCSE Centered on Students: Validation of Learning Demands and Teacher Support Scales - Doménech-Betoret, Fernando; Gómez-Artiga, Amparo; Abellán-Roselló, Laura; Rocabert-Beút, Esperanza (Frontiers in Psychology, 2020)
Based on The Educational Situation Quality Model (MOCSE, acronym in Spanish) framework, the primary objective of this study is to test the factorial validity and reliability of two MOCSE measure instruments referred to the preactional-decisional phase, specifically to learning demands and teacher supports perceived by students to overcome such demands in the classroom context. The participants were 357 Spanish undergraduate students. The data obtained by exploratory and confirmatory factor analyses revealed that the “Learning Demands Scale” (MOCSE-LDS) has a two-factor structure: perceived desirability and feasibility of demands. The data also revealed that the “Teacher Support Questionnaire” (MOCSE-TSQ) is composed of ten independent factors or subscales with good psychometric validity and reliability properties. Finally, the Student’s t-test generally indicated that the constructs considered in the instruments did not differ in gender terms. In short, the results obtained for the validity and reliability of the two tested instruments were good. Thus, the application of instruments MOCSE-LDS and MOCSE-TSQ is satisfactorily supported by empirical data. The resulting scales can be useful for researchers and teachers. On the one hand, this study provides researchers with two valid and reliable tools that may contribute to investigate students’ motivation in the university classroom context based on MOCSE postulates. On the other hand, the two tested instruments may provide teachers and school psychologists with important information to implement preventive or intervention actions to improve students’ intention to learn. Teachers may also use them to evaluate their own teaching and to research their own classrooms. The implications for education according to MOCSE postulates are discussed.